2017
DOI: 10.1088/1748-9326/aa5c42
|View full text |Cite
|
Sign up to set email alerts
|

Toward a nitrogen footprint calculator for Tanzania

Abstract: We present the first nitrogen footprint model for a developing country: Tanzania. Nitrogen (N) is a crucial element for agriculture and human nutrition, but in excess it can cause serious environmental damage. The Sub-Saharan African nation of Tanzania faces a two-sided nitrogen problem: while there is not enough soil nitrogen to produce adequate food, excess nitrogen that escapes into the environment causes a cascade of ecological and human health problems. To identify, quantify, and contribute to solving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…In most countries, production of legumes and seafood is the most efficient while the production of beef is the least efficient in terms of Nr use678923 (Table 1, Supplementary Table 4). Although vegetables and fruits have large VNFs because of low N use efficiency in these production systems2425, the Nr loss per serving of vegetables or fruits is low due to the very low N content compared to other food types9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most countries, production of legumes and seafood is the most efficient while the production of beef is the least efficient in terms of Nr use678923 (Table 1, Supplementary Table 4). Although vegetables and fruits have large VNFs because of low N use efficiency in these production systems2425, the Nr loss per serving of vegetables or fruits is low due to the very low N content compared to other food types9.…”
Section: Discussionmentioning
confidence: 99%
“…Although vegetables and fruits have large VNFs because of low N use efficiency in these production systems2425, the Nr loss per serving of vegetables or fruits is low due to the very low N content compared to other food types9. Beef production is the least efficient way of using N and supplying dietary protein in most countries that have completed their calculation of VNFs678923, mainly due to the large feed requirements and their high basal metabolic rate26. An analysis of the environmental impacts of the various livestock categories in the United States had a consistent finding6827.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to AE N , indices related to environmental sustainability like N budgets (Leip et al 2011;Eurostat 2013;Özbek and Leip 2015) and N footprint Hutton et al 2017) are important for informing practices and policies intended to minimise N loss to the environment, while optimising crop and energy production. Good N management must therefore reduce both N accumulation (Vitousek et al 2009;Leip et al 2011) and N mining (Edmonds et al 2009;Bekunda et al 2010;Kihara et al 2015), which can be detected through N budgets, as both have negative environmental impacts.…”
Section: N Budgets and N Footprintmentioning
confidence: 99%
“…The N footprint tool is useful for identifying hotspots of N losses to the environment, simulating mitigation options, and informing policy decisions for good N management through raising awareness of social responsibilities Davidson et al 2016). The application of the tool showed that in many countries the largest portion of the N footprint was associated with food production, with N accumulation in selected countries like the United States of America, whereas N mining occurred in countries like Tanzania in SSA (Hutton et al 2017). Nitrogen footprint assessments would therefore represent a great opportunity to reduce N mining in SSA through identification of potential N available for recycling in crop production.…”
Section: Table 3 Effect Of Adding Phosphorus (P) and Potassium (K) Tmentioning
confidence: 99%
“…Likewise, introducing more fertilizer in low-N areas (Sub-Saharan Africa: see also Hickman et al 2015) will have less effects on emissions than otherwise expected-at least as long as uniform conditions apply. Hutton et al (2017) point out that for Tanzania only 10% of farms receive all the mineral fertilizer available-if we assume that additional fertilizer is not just distributed on all farms evenly, but just extends the share of farms receiving fertilizer, the non-linearity effect disappears. Appropriate allocation of fertilizer application in future scenarios thus will remain a challenge.…”
Section: Discussion and Sensitivitiesmentioning
confidence: 99%